ANALISIS KEJADIAN STRES TERHADAP PEMERIKSAAN RAPID DIAGNOSTIC TEST COVID-19 PADA PEGAWAI DI RSUD BAHTERAMAS PROVINSI SULAWESI TENGGARA - endemis endemis endemis; La Ode Muhamad Sety; Irma Irma (Endemis Journal, 2021)
Stress can be seen as an emotional reaction that is quite often felt during pandemics. PDSKJI conducted a survey on mental health of 1,552 respondents, as many as 80% of respondents had symptoms of psychological posttraumatic stress due to experiencing or witnessing unpleasant events related to COVID-19. One of the strategies implemented by the Ministry of Health to control COVID-19 disease is the expansion of COVID-19 screening. However, there are many rejections from the public to carry out RDT COVID-19 examinations. This study aims to find out for differences in stress based on physiological and psychological aspects of RDT COVID-19 examination on employees at Bahteramas Hospital in Southeast Sulawesi Province in 2020. This research uses a type of quantitative research with comparative design. The population in this research is 1,060 employees and a sample of 290 employees. The sampling techniques in this study used stratified random sampling propotional techniques and used Mann Whitney statistical tests. The results showed a significant difference in stress in the fiological aspect between management and non-management employees (p-value = 0.040 < 0.05) against the examination of RDT COVID-19, on the contrary there was no significant difference in stress on the psychological aspect between management employees and non-management (installation employees) (p-value = 0.356 > 0.05) to RDT COVID-19 examination. The conclusion is that there are differences in stress based on physiological aspects and no differences in stress based on psychological aspects of RDT COVID-19 examination at Bahtramas Hospital in Southeast Sulawesi Province